Rainfall Variability and Its Influence on P Palm Oil Productivity (Elaeis Guineensis Jacq.): Case Study at PT. Nusaina Group Seram Island Province Maluku - Patty, Jacob R.; Laimeheriwa, Semuel; Madubun, Elia L.; Lingga, Sandivo (Future Science / FSH-PH Publications, 2024)
Rainfall variability significantly influences plant productivity; including palm oil. This research aims to describe rainfall variability and its influence on oil palm productivity on Seram Island, Maluku Province. The data collected consists of rainfall, palm oil production data and supporting data. The analytical method used consists of generating rainfall data, analyzing extreme rainfall conditions and regression analysis to see the relationship between rainfall and palm oil productivity. The research results show that the El Nino rainfall anomaly at the research location in the 1992-2021 period occurred 8 times with a frequency of once every 2 - 6 years or an average of once every 3 years. La Nina occurs 7 times with a frequency of 1 – 10 years or an average of once every 4 years. The very extreme El Nino caused a reduction in rainfall at the research location by 888 mm or 40% of normal conditions, whereas the very extreme La Nina event resulted in an increase in rainfall of 1491 mm or 58% of normal conditions. Rainfall variability is very closely related to oil palm productivity with the regression equation Y = 94.05 – 0.1558x + 0.000083x 2 – 10 -8 x 3 and the accuracy level R 2 is 98.6%.